The Role-Set Framework of the Satgas PPA in the Prevention and Initial Response to Sexual Violence - Fandi Prima Putra Sasono; Rachmad Kristiono Dwi Susilo; Hevi Kurnia Hardini (Jurnal Perempuan dan Anak, 2026)
Sexual violence in densely populated urban areas requires effective community-based protection mechanisms. This study analyzes the role-set framework of the Task Force for the Protection of Women and Children (Satgas PPA) in Wonokusumo Village in preventing and providing early responses to sexual violence cases, employing Robert K. Merton’s role-set theory. Using a qualitative intrinsic case study design, data were collected through in-depth interviews, observation, and documentation, and analyzed using pattern-matching techniques. The findings demonstrate that the effectiveness of the Satgas is shaped by its ability to manage an interconnected network of roles involving the local government as the source of formal legitimacy, a partnering NGO as the provider of technical capacity, and the community as a partner in early detection and victim support. Role strain emerges from limited resources and public expectations that exceed the task force’s formal mandate; however, adaptive strategies grounded in cultural approaches and internal solidarity enable the organization to sustain its functions. This study contributes to the empirical application of role-set theory in grassroots protection systems and underscores that effective women and child protection at the village level depends on the capacity of local actors to negotiate and align multiple roles within specific social contexts.